Superovulation and post-superovulatory fertility of Holstein cows under tropical conditions - SHARMA, R K; SIDDIQUF, M U; GORANI, S (The Indian Journal of Animal Sciences, 2014)
The aim of this study was to evaluate the superovulatory response. embryo yield and post-superovulatory fertility ofHolstein donor cows under tropical conditions. Fitly purebred Holstein cows were superovulated with follicle stimulatinghormone administered twice daily for 4 days by intramuscular (i.m.) injections. Donor cows were superovulated and usedfor embryo collection twice and then returnecl to normal breeding programme after 1 oestrus cycle of sexual rest. Themean ovulation rate, total and viable embryos were higher at the second than at the tirst superovulation. Animalssuperovulated during the early stage of lactation produce fewer viable embryos at tirst superovulations as compered tothose superovulated during the later stage. The mean interval between calving to first collection was 88.7±3.31 days andinterval between 2 collections was 62.5±4.87 days. The intervals from second collection to first insemination. secondcollection to conception and calving to conception were 56.8±6.46, 119.2± 15.05 and 263.2± 15.54 days respectively.When compared to control cows. two-time superovulation and embryo collection in donor cows resulted in an addition of164.5 days between calving to conception. The overall means number of services per conception was 2.6. Majority (76.6%) of donor cows conceived within 3 inseminations (services per conception 1.5) whereas, the remaining donor cows (23.4%) required a mean of 6.4 services per conception.